Antimicrobial activity of Medicinal plant extracts: A Review Article - aziz, fitua; Yousif Jasim, Suzan; E. Abdalah, Mayssaa; Saleh Mahdi, Amer (Libyan Journal of Medical and Applied Sciences, 2026)
The inappropriate uses of antibiotics have led to antimicrobial resistance, making various currently available antibiotics ineffective. Thus, there is an increasing need for the development of new antimicrobial materials that can reduce antibiotics use and overcome the emergence of resistance. Medicinal Plants could be a promising solution for fighting against disease. They contain variety of bioactive compounds such as alkaloids, quinones, tannins, terpenoids, flavonoids, and polyphenols, that have proved to have antimicrobial activity. demonstrate broad-spectrum antimicrobial activity through multiple mechanisms including membrane disruption, cell wall interference, inhibition of protein and nucleic acid synthesis, reactive oxygen species generation, and anti-virulence effects. Recent studies document measurable antimicrobial potency with minimum inhibitory concentrations in the low microgram per milliliter range against clinically relevant pathogens, including multidrug-resistant strains. They may inhibit the growth of bacteria, viruses and fungi by different mechanisms. This review explores the antimicrobial activity of bioactive compounds of medicinal plants and their possible mechanisms of action